The Expression and Effection of MicroRNA-499a in High-Tobacco Exposed Head and Neck Squamous Cell Carcinoma: A Bioinformatic Analysis - Gong, Shi-Qi; Xu, Meng; Xiang, Ming-Liang; Shan, Ya-Min; Zhang, Hao (Frontiers in Oncology, 2019)
Background: Few studies have directly investigated the differential expression of microRNAs (miRNAs) in head and neck squamous cell carcinoma (HNSCC) with low, medium, and high tobacco exposure. The purpose of this study is to screen the differentially expressed miRNAs and to investigate their clinical significance and potential biological mechanisms in the three groups of HNSCC. Methods: The datasets of HNSCC were obtained from The Cancer Genome Atlas (TCGA). The edgeR package was used to determine differentially expressed miRNAs and genes among the three groups of HNSCC. Statistical methods were applied to assess the clinical significance of miRNA and its correlation with genes. The correlation between gene expression and clinical characteristics was analyzed using weighted gene co-expression network analysis (WGCNA). Three online databases were used to predict the target genes of miRNAs. More importantly, qRT-PCR was employed to verify the differential expression of miRNAs and genes in our patients. Results: 32 differentially expressed miRNAs and 1,820 differentially expressed genes were found among the three groups of HNSCC. Patients with high expression of hsa-miR-499a had lower overall survival than the ones with low expression in high-tobacco exposed HNSCC. Cox regression analysis found that high expression of hsa-miR-499a and female were independent risk factors for prognosis in high-tobacco exposed HNSCC. Chi-square test found that hsa-miR-499a was associated with N stage in high-tobacco exposed HNSCC. WGCNA identified four gene modules associated with N stage in high-tobacco exposed HNSCC. Then three online databases were used to predict potential target genes for hsa-miR-499a, which were AEBP2 and ZNRF1. Pearson correlation analysis showed that hsa-miR-499a was negatively correlated with AEBP2 and ZNRF1. qRT-PCR supported bioinformatic results that hsa-miR-499a, AEBP2, and ZNRF1 were differentially expressed among the three groups of HNSCC in our patients. Conclusion: 32 differentially expressed miRNAs and 1,820 differentially expressed genes were successfully identified in HNSCC with low, medium, and high tobacco exposure. The patients with high expression of hsa-miR-499a had poor prognoses compared with patients with low expression in high-tobacco exposed HNSCC. Hsa-miR-499a was associated with N stage in high-tobacco exposed HNSCC. AEBP2 and ZNRF1 were the potential target genes of hsa-miR-499a.